Point-of-care ultrasound use in patients with cardiac arrest is associated prolonged cardiopulmonary resuscitation pauses: A prospective cohort study. (January 2018) - Clattenburg, Eben J; Wroe, Peter; Brown, Stephen; Gardner, Kevin; Losonczy, Lia; Singh, Amandeep; Nagdev, Arun
Abstract: Objective: We aim to evaluate if point-of-care ultrasound use in cardiac arrest is associated with CPR pause duration. Methods: This is a prospective cohort study of patients with cardiac arrest (CA) presenting to an urban emergency department from July 2016 to January 2017. We collected video recordings of patients with CA in designated code rooms with video recording equipment. The CAs recordings were reviewed and coded by two abstractors. The primary outcome was the difference CPR pause duration when POCUS was and was not performed. Results: A total of 110 CPR pauses were evaluated during this study. The median CPR pause with POCUS performed lasted 17 s (IQR 13 − 22.5) versus 11 s (IQR 7 − 16) without POCUS. In addition, multiple regression analysis demonstrated that POCUS was associated with longer pauses (6.4 s, 95%CI 2.1- 10.8); ultrasound fellowship trained faculty trended towards shorter CPR pauses (-4.1 s, 95%CI −8.8–0.6) compared to non-ultrasound fellowship trained faculty; and when the same provider led the resuscitation and performed the POCUS, pause durations were 6.1 s (95%CI 0.4 −11.8) longer than when another provider performed the POCUS. Conclusion: In this prospective cohort trial of 24 patients with CA, POCUS during CPR pauses was associated with longer interruptions in CPR.